MINATBERWIRAUSAHA MAHASISWA D3 TATA BUSANA FT-UNP - Sari, Ilva Ananta; Ernawati, Ernawati; Izwerni, Izwerni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
Operationally, the aim of this research is to reveal the description of entrepreneurship desire among D3 fashion department students FT UNP Padang, from 3 indicators which are (1) internal support (2) social motive, (3) emotional factor. This research is quantitative descriptive that show and describe the subject that researched. The population of this research is all D3 fashion department students who has been registered on January â€“ June 2013. And the sample is all population using total sampling. The data consist of primary and secondary data that get by using questionnaire. The data processed by using percentage method. The result shows that 75.35% respondents have middle internal support. 87.16% respondents have high social motive. 88.18% respondents have high emotional factors. Generally, 82.20% respondents have high factors that affect entrepreneur desire. Â Kata kunci: Minat, Berwirausaha, Mahasiswa Tata Busana